Two-dimensional MXene-based nano-prodrug for synergistic chemo-photothermal therapy on cancer treatment - Wang, Jinyu; Qiao, Qianqian; Feng, Yuqi; Guo, Yuhao; Liao, Tao; Li, Linwei; Kuang, Ying; Jiang, Bingbing; Xu, Ziqiang; Li, Cao (Materials today chemistry, 2024)
In cancer treatment, although prodrugs have been developed to overcome obstacles such as undesirable pharmacokinetic performance and serious off-target toxicity of most chemotherapeutics, the combination of prodrugs with nanotechnology could be used to overcome the shortcomings of conventional prodrug strategies and facilitate more efficient drug delivery and accumulation of anticancer prodrugs at specific sites/tissues. Phototherapy is a method that uses near-infrared (NIR) light to achieve local and non-invasive tumor therapy. The combination of chemotherapy and phototherapy has shown many therapeutic advantages, including synergistic therapeutic effects and the reduction of toxic and side effects of drugs through dose reduction. In this work, a hydrazone linkage was reported to conjugate Ti3C2Tx MXene nanosheets with doxorubicin hydrochloride (DOX) and methoxy poly(ethylene glycol) benzaldehyde (mPEG-CHO) through a chemical surface modification to form a two-dimensional (2D) nano-prodrug Ti3C2Tx-DOX/PEG (TDP) for synergistic chemo-photothermal therapy. First, hydrazide functionalized Ti3C2Tx was obtained. Then, the carbonyl group of DOX and the aldehyde group of mPEG-CHO can form a pH-responsive hydrazone bond with hydrazide-functionalized Ti3C2Tx. The high surface area of Ti3C2Tx could overcome the reduced drug loading caused by conjugation. Aqueous stability and biocompatibility were enhanced by the introduction of PEG, making the material capable of prolonged circulation in the body's bloodstream. By achieving excellent antitumor results with this nano-prodrug, we have added another brick to the edifice of Ti3C2Tx MXene as an anticancer drug carrier, and given new vitality to the study of anticancer prodrugs combined with nanotechnology. •Nano-prodrug based on Ti3C2Tx MXene was prepared for synergistic cancer therapy.•Combination therapy ensures low drug dosage and good biosafety.•pH-trigged drug release combined with PTT results in good tumor suppression.